A web-based computer-program grading system - Li, Junqiang. (2013)
Programming is a fundamental skill for most engineering students, and millions of programming assignments are conducted every year in higher education community. However, without an efficient and easy-to-use tool, it is hard for instructors to grade students’ programming assignments and detect source code plagiarism.